2014
DOI: 10.1002/bjs.9437
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score analysis of oesophageal cancer treatment with surgery or definitive chemoradiotherapy

Abstract: There was no difference in survival after oesophageal cancer treatment involving surgery or dCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
0
22
0
10
Order By: Relevance
“…6,7 A number of retrospective cohort studies have shown that the rates of survival of patients with esophageal cancer who undergo definitive CRT are similar to those in patients who receive surgical treatment approaches. 812 Motoori et al 11 enrolled 173 patients with clinical T1bN0M0 squamous cell carcinoma of thoracic esophagus. In the study, 102 patients were treated with esophagectomy and 71 patients with definitive CRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 A number of retrospective cohort studies have shown that the rates of survival of patients with esophageal cancer who undergo definitive CRT are similar to those in patients who receive surgical treatment approaches. 812 Motoori et al 11 enrolled 173 patients with clinical T1bN0M0 squamous cell carcinoma of thoracic esophagus. In the study, 102 patients were treated with esophagectomy and 71 patients with definitive CRT.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant overall survival difference between 2 groups. Karran et al 12 retrospectively studied 521 patients with clinical stage I–IVa esophageal cancer (277 in the surgery and 244 in the definitive CRT). They performed propensity score analysis to eliminate the selection bias and found there was no difference in survival after esophageal cancer treatment involving surgery or definitive CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Karran et al 18 reported a study of 727 esophageal cancer patients and used regression adjustment to create a cohort of 521 patients who were available for comparison (277 patients in the surgery group and 244 patients in the CCRT group). The median survival, and 2- and 5-year survival rates after surgery were 27 months, 53.8% and 31.0%, respectively, compared with 28 months, 54.2% and 31.9% after CCRT (p=0.918).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few studies comparing the definitive CCRT with surgery alone for esophageal cancer, most of which are prospective Phases I and II clinical trials and retrospective studies, [20][21][22] and only a few of which are randomized clinical trials. 23 Teoh et al 23 reported a randomized trial of 81 patients with operable SCC of the mid-or lower thoracic esophagus with a 5-year OS favoring CRT, although it was not statistically significant (surgery 29.4% and CRT 50%; P=0.147).…”
Section: Surgery Vs Definitive Crt For Esophageal Cancermentioning
confidence: 99%